Hydrogen Peroxide Affects Growth of S. aureus Through Downregulation of Genes Involved in Pyrimidine Biosynthesis - Buvelot, Hélène; Roth, Myriam; Jaquet, Vincent; Lozkhin, Andrey; Renzoni, Adriana; Bonetti, Eve-Julie; Gaia, Nadia; Laumay, Floriane; Mollin, Michéle; Stasia, Marie-José.; Schrenzel, Jacques; François, Patrice; et al. (Frontiers in Immunology, 2021)
Reactive oxygen species (ROS) play a crucial role in the cellular defense against S. aureus, as evidenced by the importance of this pathogen in patients lacking the ROS-generating phagocyte NADPH oxidase NOX2. ROS concentrations required to kill S. aureus in vitro are much higher than those found in the phagosome. We therefore hypothesized that sublethal ROS concentrations may play a role in S. aureus gene dysregulation and investigated the in vitro transcriptomic response of S. aureus to sublethal concentrations of hydrogen peroxide (H2O2). A striking observation of these experiments was a coordinated and massive downregulation of genes involved in pyrimidine metabolism. Using transposon insertion mutants, we demonstrated that deletion of carA, a gene involved in pyrimidine synthesis, led to a significant growth defect and to an increased sensitivity of S. aureus to added H2O2. The phenotype of the carA mutant could be reversed through supplementation with the pyrimidine precursor uracil, or with a multicopy vector encoding carA. As opposed to the impact of ROS on extracellular survival, carA deletion did not affect the intracellular survival in neutrophils. Our results raise the possibility that ROS-dependent downregulation of pyrimidine metabolism might be a survival strategy of S. aureus, allowing colonization through intracellular survival, while decreasing the risk of killing the host through dampened extracellular growth.